Analisis Profitabilitas Dalam Menilai Kinerja Keuangan Pada PT. Taspen (Persero) Medan - Sanjaya, Surya; Rizky, Muhammad Fajri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Profitability ratio is the ratio that aims to find out the company's ability to generate a profit during a certain period and also gives an overview of the effectiveness of the management in the conduct of operations. Effectiveness here seen from the resulting profits against sales and investment company. The policy of the company taken in determining profit can be seen from the level of profitability. This research aims to find out the cause of the Return On Asset (ROA) tends to decline and Return On Equity (ROE) in 2015 to 2016 decline. This research uses descriptive method, and data collection techniques used in this research is the engineering documentation. Return On Asset (ROA) tends to decline, this dikarenankan decrease in the sale of the company so that company earnings will also decrease and the value of the ROA from the year 2012 to 2016 do not meet the standards of the assessment of the Ministry of STATE-OWNED ENTERPRISES SOES PER-10/MBU/ 2014 and Return On Equity (ROE) in 2015 to 2016 has decreased, this shows the company is not able to generate a return on equity that is owned.